2004
DOI: 10.1079/bjn20041181
|View full text |Cite
|
Sign up to set email alerts
|

Olive oil and its main phenolic micronutrient (oleuropein) prevent inflammation-induced bone loss in the ovariectomised rat

Abstract: The present study was designed to evaluate the effect of olive oil and its main polyphenol (oleuropein) in ovariectomised rats with or without inflammation. Rats (6 months old) were ovariectomised or sham-operated as control. Ovariectomised rats were separated into three groups receiving different diets for 3 months: a control diet with 25 g peanut oil and 25 g rapeseed oil/kg (OVX), the control diet with 50 g olive oil/kg or the control diet with 0·15 g oleuropein/kg. The sham-operated group was given the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
80
0
9

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(96 citation statements)
references
References 39 publications
7
80
0
9
Order By: Relevance
“…Furthermore, animal studies have shown that virgin olive oil prevents inflammation-induced bone loss (Puel et al, 2004), thus providing a potential mechanistic support to our findings. The reduced risk of fractures associated with high HDL-cholesterol level is consistent with the protection observed for MUFA, because a high MUFA intake, typical of the Mediterranean food pattern, has been repeatedly shown to increase HDL levels (Mensink and Katan, 1992;Mensink et al, 2003;Esposito et al, 2004).…”
Section: Discussionsupporting
confidence: 79%
“…Furthermore, animal studies have shown that virgin olive oil prevents inflammation-induced bone loss (Puel et al, 2004), thus providing a potential mechanistic support to our findings. The reduced risk of fractures associated with high HDL-cholesterol level is consistent with the protection observed for MUFA, because a high MUFA intake, typical of the Mediterranean food pattern, has been repeatedly shown to increase HDL levels (Mensink and Katan, 1992;Mensink et al, 2003;Esposito et al, 2004).…”
Section: Discussionsupporting
confidence: 79%
“…Digestion with trypsin yielded the four expected A␤ fragments: [1][2][3][4][5], [6 -16], [17][18][19][20][21][22][23][24][25][26][27][28], and [29 -40] following cleavage after arginine (R) or lysine (K) residues (Table 2), as well as partially cleaved fragments ( Table 3). The soft ESI ionization also enabled the detection of noncovalent interactions between sequential and nonsequential fragments.…”
Section: Resultsmentioning
confidence: 99%
“…Noncovalent interactions of peptide fragments with OE, added before digestion, were detected for the [17][18][19][20][21][22][23][24][25][26][27][28] fragment of A␤ (Figure 2) and the partially cleaved peptide fragments [6 -28] and [6 -40]. In addition, noncovalent complexes of OE with the [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] fragment, derived from the chymotryptic activity of the enzyme, was also detected.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations